Stressors affected emotional and physiological exhaustion among volunteers during second wave of covid-19 pandemic - Oda Debora; Sulistyono (STIKep PPNI Jawa Barat, 2021)
Aims: Our government summon up many resources during combating Covid-19 pandemic, including volunteers which has many backgrounds. Their domain mainly at pre-hospital area, but remain at high risk contracted by covid-19 virus. The purpose of this study was to analyze dominant threat which was perceived by volunteers which could affected emotional exhaustion and physiological stress in volunteers during second wave Covid-19 pandemic. Design: This research was descriptive study using cross-sectional design. Methdos: Respondents were taken by simple random sampling technique and 100 respondents were obtained during early December 2020 to end of January 2021. Smart Partial Least Square 3.0 was used as multivariate analysis. Results : The analysis showed that t stat 8,766 (>1,96) and p values 0,000 (< 0,05), which means there was a direct influence between perceived emotional threat and emotional exhaustion. The second result showed that t stat 8,078 (> 1,96) and p values 0,000 (< 0,05), which means there was a direct influence between perceived emotional threat and physiological anxiety. Conclusions : This study showed that perceived emotional threat was the main stressor which affect emotional exhaustion and physiological anxiety .This stressors are mental health issues among volunteer during Covid-19 pandemic and need to be handled as it can increase body vulnerability to SARS-COV-19 virus. This research sampling technique was accidental sampling, so the result of this study mainly represent the condition of Malang Covid-19 volunteers. A better sampling technique might be required to get a better result and population generalization